Adequacy of information provided by the Algerian Standards on Auditing concerning the audit engagement letter - Comparative study between the audit engagement letter used in the Algerian auditing field and the audit engagement letter of Deloitte & Touc - azouaou, ahmed rami; touirat, rabeh (Journal of Research in Finance and Accounting, 2025)
This study aims to know the adequation of the information of the audit engagement letter used in the Algerian auditing filed, the study provides a comparison between the audit engagement letter of Deloitte & Touche LLP and the audit engagement letter used in the Algerian auditing field, also comparing the audit engagement letter used in the Algerian auditing with the audit engagement letter provided by the Algerian standard on auditing 210 “agreeing audit engagement terms”. The results of this study clarifies that the audit engagement letter used in the Algerian auditing filed lack of most important information, which is required for improving audit engagement procedures, counter to the audit engagement letter of Deloitte & Touche LLP, the information provided was well detailed about audit engagement.